2019
DOI: 10.35649/kubr.2018.13.12.2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Consumer Purchase Intention of Life Insurance: Bangladesh Perspective

Abstract: Purpose- The purpose of this paper is to investigate the factors affecting customer intention to purchase life insurance. Design/Methodology/Approach- Based on a sample of 200 individuals, this study is basically descriptive in nature and used both primary and secondary sources of data. To investigate the relationship between dependent and independent variables one way ANOVA tests, Correlation and Multiple Regression Analysis were conducted throughout the research. Findings- The paper demonstrates that socio-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…At a macro-economic level, a positive link has been predicted between risk aversion and insurance consumption of a nation (Hofstede, 1995;Schlesinger, 1981;Szpiro, 1986). Further, it is posited that an individual with a risk aversion motive will always prefer less risk (Ofoghi & Farsangi, 2013;Outreville, 1998), indicating an individual's proclivity towards purchasing insurance (Chiappori & Salanié, 2000;Emamgholipour et al, 2017;Jahan & Sabbir, 2018). In line with this, the following hypothesis is put forward in this study:…”
Section: Risk Aversion Motives (Ram)mentioning
confidence: 57%
See 4 more Smart Citations
“…At a macro-economic level, a positive link has been predicted between risk aversion and insurance consumption of a nation (Hofstede, 1995;Schlesinger, 1981;Szpiro, 1986). Further, it is posited that an individual with a risk aversion motive will always prefer less risk (Ofoghi & Farsangi, 2013;Outreville, 1998), indicating an individual's proclivity towards purchasing insurance (Chiappori & Salanié, 2000;Emamgholipour et al, 2017;Jahan & Sabbir, 2018). In line with this, the following hypothesis is put forward in this study:…”
Section: Risk Aversion Motives (Ram)mentioning
confidence: 57%
“…Further, to test the significance of particular psychological and behavioural factors in predicting purchase intention towards life insurance alongside attitude and subjective norms, religiosity, risk aversion motives, and saving motives were included in the classical TRA model. Past studies have reported the robustness of religiosity, risk aversion motives, saving motives, and financial literacy as direct antecedents of life insurance demand (Mahdzan & Victorian, 2013), and purchase intention towards life insurance (Buzatu, 2013;Jahan & Sabbir, 2018) and Islamic life insurance (Zakaria et al, 2016). However, the integration of such factors within the classical TRA model is quite unlike in extant literature.…”
Section: Theory Of Reasoned Actionmentioning
confidence: 94%
See 3 more Smart Citations